1994
DOI: 10.1016/0035-9203(94)90197-x
|View full text |Cite
|
Sign up to set email alerts
|

Control of endophagic Anopheles mosquitoes and human malaria in Guinea Bissau, West Africa by permethrin-treated bed nets

Abstract: We compared the anti-mosquito and antimalarial potentialities of placebo-treated versus permethrin-impregnated bed nets in north-western Guinea Bissau. Baseline, pre-intervention entomological and parasitological data were collected during the rainy season of 1990 and bed nets were distributed shortly before the rainy season of 1991. Pairs of 3 ethnically different villages were investigated. The villages in each pair were at least 2 km apart but belonged to the same ethnic group in an ecologically similar are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 11 publications
2
30
1
Order By: Relevance
“…The prevalence of malaria in the community is low. In 1990, a survey of children two-nine years old in rural GuineaBissau showed that P. falciparum was the most prevalent parasite (Jaenson et al 1994).…”
mentioning
confidence: 99%
“…The prevalence of malaria in the community is low. In 1990, a survey of children two-nine years old in rural GuineaBissau showed that P. falciparum was the most prevalent parasite (Jaenson et al 1994).…”
mentioning
confidence: 99%
“…Variations in mosquito abundance over time exist. Jaenson et al (1994) recorded lower mosquito abundance indoors in 1991 compared with 1990, despite the higher rainfall in 1991. More mosquitoes were also caught in light traps outdoors in 1993 than in 1994 in Antula.…”
Section: Discussionmentioning
confidence: 62%
“…Malaria is stable in the area with parasite rates of 10-50% at the end of the rainy season and spleen rates ranging from 10% to 50% among 2-9-year-old children. 17,18 It is common for children in the study area to sleep under bed nets. 19 Study population and definitions.…”
Section: Methodsmentioning
confidence: 99%